2015
DOI: 10.1002/jsfa.7380
|View full text |Cite
|
Sign up to set email alerts
|

Ingenane-type diterpene compounds fromEuphorbia kansuimodulate IFN-γ production through NF-κB activation

Abstract: These findings suggest that E. kansui enhances IFN-γ secretion through the NF-κB pathway in NK cells. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…However, NF-κB site was also identified within the promoter region of IFN-γ gene demonstrating that NF-κB may be involved in the molecular mechanisms controlling gene transcription of IFN-γ in human T lymphocytes [ 78 ] which could directly explain the relationships between SIRT1 and IFN-γ observed in our studies. This signaling pathway was then confirmed in other studies performed on human NK-92 cells [ 81 , 82 ].…”
Section: Discussionsupporting
confidence: 78%
“…However, NF-κB site was also identified within the promoter region of IFN-γ gene demonstrating that NF-κB may be involved in the molecular mechanisms controlling gene transcription of IFN-γ in human T lymphocytes [ 78 ] which could directly explain the relationships between SIRT1 and IFN-γ observed in our studies. This signaling pathway was then confirmed in other studies performed on human NK-92 cells [ 81 , 82 ].…”
Section: Discussionsupporting
confidence: 78%
“…8 of these met with the criteria that had OB ≥ 30% and DL ≥ 0.18 [34]. In addition, 13 compounds below this specification (GE05-GE08, GE12, GE14, GE15, GE17, GE18 and GE24-GE27) were also taken as the active compounds that had promising treatment to the malignant ascites [4,5,16,35]. Thus, a total of 21 compounds were selected for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ho, is a commonly used Chinese herbal medicine (CHM) and is recorded in Sheng Nungs Herbal for multiple medical applications [4]. As we know, kansui has promising biological effects on cancer [5], pancreatitis [6], immune regulation [7], intestinal obstruction [8] and diabetes [9]. Among these, kansui is particularly applied to edema, ascites and asthma [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terpenoid compounds derived from the roots of E. kansui showed a significant inhibition of proliferative activity of embryonic cells and intestinal epithelioid cells [35, 36]. It was reported that ingenane-type diterpenes from Kansu modulated IFN- γ production by regulating nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) [37]. …”
Section: Introductionmentioning
confidence: 99%